2016
DOI: 10.1186/s12889-016-3635-3
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hazards and health cost of women cotton pickers in Pakistani Punjab

Abstract: BackgroundFarm workers and female cotton pickers are exposed to residual impacts of pesticide use in cotton production, in addition to dust, ultraviolet radiation, etc. Cotton picking causes various health hazards among cotton pickers with varied health cost. A soil bacterium known as Bacillus thuringiensis (Bt) is incorporated in cotton seed through genetic modification and it has resistance against certain bollworms of cotton. So it is considered that Bt cotton fields have less pesticide exposure compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…For example, for Pakistan we derived 81,750 non-fatal UAPP in 2010. However, this was based on studies of female cotton pickers only [39,162] and we refrained from extrapolating this figure, which was based on a subpopulation of agricultural workers, to the total population. For Zambia, no national estimate was derived although one paper was extracted [179], as this study reported data from two hospitals with no clear catchment area stated Table 3 Examples for sampling strategies used in studies Without random sampling: "Present study was conducted in the southern Punjab i.e.…”
Section: National Estimates Of Uappmentioning
confidence: 99%
“…For example, for Pakistan we derived 81,750 non-fatal UAPP in 2010. However, this was based on studies of female cotton pickers only [39,162] and we refrained from extrapolating this figure, which was based on a subpopulation of agricultural workers, to the total population. For Zambia, no national estimate was derived although one paper was extracted [179], as this study reported data from two hospitals with no clear catchment area stated Table 3 Examples for sampling strategies used in studies Without random sampling: "Present study was conducted in the southern Punjab i.e.…”
Section: National Estimates Of Uappmentioning
confidence: 99%
“…Third, the study has focused on the role of Bt technology and has not analyzed the potential of other possible interventions–such as strengthening extension services and supporting the spread of knowledge about pesticide safety–that could also help to reduce pesticide-related health cost [43]. Fourth, this study ignores the health impacts of pesticide reduction on casual workers, especially female workers who are often involved in the cotton harvest [4748]. Future studies could explore the health effects for the different population groups involved in the cotton sector.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have observed significantly increased concentrations of pesticide residues in blood samples of pesticide operators [4546]. Cotton pickers, often poor female laborers, were also found to suffer from pesticide-related illnesses [4748]. To reduce health and environmental problems of pesticide use, in the mid-1990s farmer field schools were established in Pakistan’s major cotton-producing districts to promote low-pesticide use and integrated pest management (IPM) techniques [49].…”
Section: Cotton Production and Pesticide Use In Pakistanmentioning
confidence: 99%
“…Peak foetal length velocity occurs during the second trimester and organ maturation and weight gain occur during the third trimester. Environmental exposure to pesticides during cotton harvesting is also known to compromise the health of women in Pakistan [6], which in turn might compromise foetal development.…”
Section: Discussionmentioning
confidence: 99%
“…While paid agricultural employment can benefit rural women by increasing their social status, decision-making ability and purchasing power, excessive energy expenditure during periods of intensive agriculture work and exposure to toxic chemicals, such as pesticides, can compromise maternal nutrition and health [3, 6]. Pregnant women involved in labour-intensive work such as cotton harvesting are at particularly high risk.…”
Section: Introductionmentioning
confidence: 99%